Síntese e caracterização estrutural de filmes finos de ZnO dopados com Co preparados por Dip-Coating - Valério, Luis Renato (2016)
The interest in developing magnetic semiconductor materials for application in the developing of spintronic devices has attracted attention of researchers in recent years. Alloys of semiconductor material oxides such as ZnO, TiO2 and SnO2, and transition metals such as Co, Mn and Fe forms systems that potentially present room temperature ferromagnetism, making them candidates for use in spintronics. This subclass of materials are usually called diluted magnetic oxides. However, in spite of the big number of the experimental and theoretical reports related to this subject, the nature of ferromagnetism usually observed is still a controversial issue. Recently, experimental results indicate that the origin of the ferromagnetic order in these materials is related to the presence of structural point defects, such as vacancies and atoms in interstitial sites. In this context, here we present the studies related to the preparation and structural characterization of Co-doped ZnO thin films (Zn1-xCoxO) in the concentrations of x 0; 0,01; 0,03 and 0,05 deposited by dip-coating technique. Structural characterization was performed by X-ray diffraction, x-ray absorption spectroscopy, by photoluminescence and transmission spectroscopy. The obtained results confirm the incorporation of Co ions in ZnO wurtzite matrix structure without the formation of secondary phases, such as Co oxides or metallic Co. The scanning electron microscopy results reveal a nanostructured morphology for the prepared thin films.